ANALISIS PSIKOLOGI SASTRA DAN NILAI MORAL DARI NOVEL CINTA SUCI ZAHRANA KARYA HABIBURAHMAN EL SHIRAZY - Nayla Azkani; Rahmat Kartolo (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the Literary Psychology and Moral Values of the Novel Cinta Suci Zahra by Habiburahman El Shirazy. This research is a descriptive qualitative using a structuralism approach. The activities carried out in this study were reading, observing, interpreting and analyzing the novel Cinta Suci Zahrana. The data sources in this study are: (1) text, the novel Cinta Suci Zahrana; (2) field notes consisting of two parts, namely the description section and the reflection section. The data collection techniques used are the documentation method and the review method. From the analysis carried out, the literary psychology contained in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy is found in chapter